Effectiveness of Akupresure on Function and Time of Sensoric Improvement in Non Hemoragic Stroke Patients (Ischemia) - Dwi Hendry Saputra (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Decreased sensory function is a complication that often occurs in non-hemorrhagic stroke patients, as a result of decreased cerebral circulation. Acupressure is useful in improving sensory function by launching the movement of the flow of qi (vital energy) in the body. But not many studies have examined the effectiveness of acupressure in the function and timing of sensory repair in non-hemorrhagic stroke patients. Method The type of research used is the study True Experiment Design with aapproach randomized control trial. This study compiled two groups, namely the intervention group and the control group. Technique Probability sampling with a method simple random sampling was used to get 42 respondents divided into 2 groups. Results Test results Independentt test shows value p value 0.000 which indicates that there is a significant difference in the value of sensory function between the intervention and control groups. Conclusion The results of the study after being given an intervention that an increase in sensory function is better and faster in patients who get acupressure, so this action is effectively implemented for non-hemorrhagic stroke patients with sensory disorders.